Poznański Odwach z XVIII wieku: historia – architektura – autorstwo - Mączyński, Ryszard (Sztuka i Kultura, 2023)
The Poznań Guardhouse located in the middle of the Stary Rynek (Old Market) square is a historic monument of very fine quality which dates from the Enlightenment. It is easily recognizable due to its location at the centre of tourist routes. It is also frequently visited, and is now the seat of the Museum of the Wielkopolska Uprising of 1918–1919 – a branch of the Wielkopolska Museum of the Struggle for Independence. Publications printed to this day claim that the building was designed and erected by Johann Christian Kamsetzer, King Stanisław August’s first architect. However, this is not true. Established attributions of monuments dating from the reign of Stanisław August have been repeated many times and therefore are longlived. There would be nothing wrong with this had not many of them been made without being confirmed on the basis of source documents, or without even taking into consideration the specific context of the epoch or the artist’s background. They were made based on loose associations, without putting forward any arguments. Sometimes they contributed to whole sequences of attributions arising. One speculation led to another, and they were repeated in print, thereby creating ‘indisputable facts’. The Poznań Guardhouse is a good example of this.